2021
DOI: 10.1002/nano.202100145
|View full text |Cite
|
Sign up to set email alerts
|

Sub‐ppm sulfur dioxide detection using MoS2 modified multi‐wall carbon nanotubes at room temperature

Abstract: Sulfur dioxide (SO2) is highly toxic to environment and has an adverse effect on a living being. In this report, a chemiresistive SO2 gas sensor based on carboxylic‐acid functionalized multiwalled carbon nanotubes/molybdenum disulfide nanocomposite sensing film is reported. The receptor film was characterized with various morphological, microstructural, and compositional tools such as transmission electron microscope, X‐ray diffraction, and X‐ray photoelectron spectroscopy, respectively. The systematic investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…With a reaction of 1.81% at a concentration of 3 ppm, the test indicates its selectivity to SO 2 . 19 From the foregoing research studies, it can be concluded that LMD materials exhibit room-temperature SO 2 sensing ascendency. However, because there are few surface defect states and it is difficult to exchange electrons with gas, relatively high detection concentrations and low responsiveness can occur, making it difficult to satisfy the aforementioned industry criteria requirements.…”
Section: Introductionmentioning
confidence: 92%
“…With a reaction of 1.81% at a concentration of 3 ppm, the test indicates its selectivity to SO 2 . 19 From the foregoing research studies, it can be concluded that LMD materials exhibit room-temperature SO 2 sensing ascendency. However, because there are few surface defect states and it is difficult to exchange electrons with gas, relatively high detection concentrations and low responsiveness can occur, making it difficult to satisfy the aforementioned industry criteria requirements.…”
Section: Introductionmentioning
confidence: 92%
“…4 FeO 3 displayed the best gas sensing performance, with a sensor response of 7.6 at an SO 2 concentration of 3 ppm at a low working temperature of 120 • C. The thin film was made using the DC-sputtering technique. The sensor showed a preferential selectivity for the detection of SO 2 gas under the operating condition compared to CH 4 , CO 2 , and CO. An MWCNT/MoS 2 nanocomposite prepared via a simple chemical method was proposed as a low-energy and RT operating sensor layer [88]. The device is selective towards SO 2 gas.…”
Section: Recent Advances In So 2 Gas Sensorsmentioning
confidence: 99%
“…Air contamination with this gas is one of the causes of many respiratory (laryngitis, chronic bronchitis, respiratory tract infections), and cardiovascular diseases [14,15]. Exposure of a human organism to a concentration of SO 2 equal to 100 ppm is related to a direct threat to life [16][17][18]. The maximum exposure can not exceed 175 ppb per 10 minutes and 2 ppm per 10-hour time period according to air quality standards [17].…”
Section: Introductionmentioning
confidence: 99%
“…However, their sensitivity toward other gas molecules (including SO 2 ) was reported low in comparison. The response of TMD sheets toward selected analytes can be enhanced via substitutional doping [39][40][41][42][43][44][45][46][47][48], or decoration of their surfaces with single atoms [49], nanoparticles [50,51], and nanotubes [18]. Doping can be an effective strategy to tune the sensitiv-ity of MoS 2 sheets to a relatively wide range of gases, e.g.…”
Section: Introductionmentioning
confidence: 99%